A semi-active control method for decreasing longitudinal torsional vibration of vehicle engine system: Theory and experiments. (20th January 2019) - Bian, Yushu; Gao, Zhihui; Hu, Jiangtao; Fan, Ming
Abstract: Due to diverse working conditions, the vehicle engine system may generate complicated nonlinear whole-body vibration with wide frequency band. Since conventional vibration control methods are usually designed in terms of the external excitations and implemented based on the linear models, their performance is difficult to improve. In this study, a new semi-active vibration absorption method that is both independent of external excitations and capable of dealing with nonlinear vibration problem is put forward to decrease the longitudinal torsional vibration of the vehicle engine system. It sufficiently utilizes nonlinear coupling and modal interaction to transfer and dissipate vibration energy, rather than relies on linear neutralization. A novel vibration absorber scheme with controllable frequency and controllable damping is proposed, which can be readily implemented by the control algorithms. Numerical simulations and virtual prototyping simulations have verified the correctness of theoretical research. Experimental investigations have been carried out to successfully examine the effectiveness and the feasibility of the proposed method.